Engaging Students’ Information Literacy Ability On The 1945 Constitution Toward Android (Gejog Lesung) Based E-Learning Media - Isna Sari Rukmana; Marzuki Marzuki; Kharisma Fenditasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This study aims to analyze students' information literacy ability enhancement using android (gejog lesung) based e-learning media on the 1945 constitution. The method used in this study was a quasi-experimental method. This research used 35 students as subjects. The test used in this study aims to collect data consisting of pretest and posttest information literacy questions with HOTs criteria for information literacy skills and consisting of ten multiple-choice questions according to high order thinking skills criteria then checked for the Content Validity Index. Data analysis is using a t-test. The result of this study is gejog lesung it is able to improve students’ information literacy ability on the 1945 constitution of 1,4 in the high category. So, it can be concluded that engaging students’ ability of information literacy on the 1945 constitution toward android (gejog lesung) based e-learning media has a great influence on improving students’ information literacy ability.